Optimal management of ALK-positive NSCLC progressing on crizotinib. (April 2017) - Metro, Giulio; Tazza, Marco; Matocci, Roberta; Chiari, Rita; Crinò, Lucio
Highlights: Crizotinib is the mainstay of treatment of ALK -positive advanced NSCLC. Crizotinib beyond progression may be effective in case of oligoprogressive disease. Experience with crizotinib beyond progression refers mainly to isolated CNS relapse. Second-generation ALK-TKIs have shown activity in crizotinib-refractory patients. Optimal treatment of crizotinib-refractory patients should be individualized. Abstract: Crizotinib is an anaplastic lymphoma kinase (ALK)-tyrosine kinase inhibitor (-TKI) that represents the standard first-line treatment of patients with ALK -rearranged ( ALK -positive) advanced non-small cell lung cancer (NSCLC). In this setting, crizotinib has demonstrated a response rate of roughly 75% and a median progression-free survival just under one year. However, acquired resistance will emerge in virtually all crizotinib-treated patients, whose management may require a diversified approach according to the pace of the disease and/or the site(s) of disease progression. Crizotinib beyond disease progression is an option in patients with oligoprogressive disease, especially in presence of isolated central nervous system (CNS) relapse, provided that local ablative therapy (mainly radiotherapy) to the brain is administered. On the other hand, novel more potent and highly selective ALK-TKIs with demonstrated anti-tumor activity (CNS included) in crizotinib-refractory patients have been made available in recent years. Therefore, clinicians may well consider switching to a second-generation ALK-TKI as treatment option in case of progression on crizotinib. Therapeutic chances are more limited for patients who progress after crizotinib and a second-generation ALK-TKI, for whom both a third-generation ALK-TKI or pemetrexed-based chemotherapy could prove beneficial, while evidence in support of the use of immunotherapy in patients pretreated with ≥1 ALK-TKI is lacking.